Experimental investigation of oil retention and pressure drop of R32/PVE oil mixture in compressor suction line. (December 2021) - Zeng, Weijie; Gu, Bo; Du, Zhongxing; Zhang, Zhiting; Tian, Zhen
Highlights: Oil retention amount and pressure drop of R32 with PVE oil in suction line were measured experimentally. The influences of refrigerant mass flux, oil mass fraction, transport property and flow direction on oil retention and pressure drop were discussed. Two consolidated databases of oil retention and pressure drop were amassed to conduct comparison and analysis. Oil retention impact factor was proposed to reflect the oil transport difficulty and it integrated the influences of geometric dimension, working pairs and operation parameters. Abstract: R32/PVE oil mixture has become a popular working pair of commercial refrigeration/heat pump systems in recent years. This paper presented experimental study of oil retention and pressure drop characteristics of R32/PVE VG68 mixture in the compressor suction lines. The test samples were two smooth copper pipes of horizontal and vertical flow orientations with 10.7mm inner diameter. The oil retention in suction lines were measured based on remove-and-weight technique (RWT). Three conditions of saturation temperature and superheat degree (7.5/12, 7.5/6 and 10/12 ° C) were tested, in order to obtain different thermophysical and transport properties. Refrigerant mass flux and nominal oil mass fraction (OMFno ) were varied with the ranges of 90−230 kgm −2 ·s −1 and 1−5%, respectively. The influences of refrigerant mass flux, oil mass fraction, mixture viscosity and flow configuration on oil retention and pressure drop were investigated. The results showed that the oil retention amount tends to increase with the increases of actual oil mass fraction (OMFact ) and mixture kinematic viscosity ratio and the decrease of refrigerant mass flux. Two consolidated databases for oil retention and pressure drop of suction lines, which involved five working pairs, were collected from the existing literatures to perform a comparison. Finally, based on analysis of oil transport mechanism, a new dimensionless parameter called oil retention impact factor was proposed to characterize the difficulty of oil transport, which integrated the influences of geometric dimension, working pairs and operation parameters. It showed relatively satisfactory relationship with the oil retention data from the amassed database and the present study.